JOINT PRODUCTION SECTOR, extractive, PROCESSING AND MARKETING NEEDED TO BOOST THE ECONOMIC DEVELOPMENT OF THE COUNTRY - García Z., Teonila (2002)
It is to create the Ministry of Production in an attempt to support a national plan of production, a sector to formulate policy and direct the production, processing and extractive activity. Industrialization and commercialization of aquatic and agricultural and mining metallurgical promote, coordinate and guide his development, maximizing the productivity of each of the products you need the domestic market and for export projection.